What kind of therapeutic solutions for Graves’ disease does modern medicine propose? - a review of the literature - Woś, Natalia; Szala-Czerwonka, Karolina; Rejmer, Adrian; Rojek, Katarzyna; Bednarz, Lucjan; Wijas, Karolina; Bialic, Kinga; Bakalarczyk, Rafał; Bialic, Artur; Majewski, Paweł (Journal of Education, Health and Sport, 2023)
Background: Graves’ disease is responsible for 60-80% causes of hyperthyreosis. An important role in the pathogenesis is played by anti-TSHR immunoglobulins (TRAb), that stimulate TSH receptors leading to excessive hormone synthesis and release by the gland. The aim of the study: This study was designed to summarise the current state of knowledge on the diagnosis, pathogenesis and methods of treatment used for Graves’ disease. Materials and methods: We reviewed the literature available in the PubMed database using the following keywords: "Graves’ disease", "Graves’ pathogenesis", "Graves’ diagnosis", "Graves’ treatment”. Results: Graves’ disease develops as a result of as well genetic as environmental factors. The diagnosis is based on physical examination, and laboratory & imaging studies. Several therapeutic options are currently used. Pharmacotherapy with thyreostatics is used either as a stand-alone method or as a preparation for a radical treatment - radioactive iodine ablation and thyroidectomy, which is the surgical removal of the gland. The treatment form is recommended to be selected individually depending on each patient, indications and co-morbidities. Developing research into the etiology of the disease is an opportunity to develop newer and efficient methods of causal treatment. Summary: Graves’ disease is an autoimmune thyroid disorder with a multiple factor etiology. A variety of therapeutic approaches are currently used: treatment with antithyrodid drugs, radioactive iodine ablation and the surgical resection of the thyroid gland. A more detailed understanding of the mechanisms causing the development of the disease offers prospects for the creation of innovative and more efficient therapeutic modalities.